Incidencia de las estrategias metodológicas para la enseñanza-aprendizaje de la asignatura emprendimiento y gestión en el primer año de bachillerato general unificado de la Unidad Educativa San Camilo - Orbe Herrera, Juliana Katherine (2017)
This research work aims to highlight the importance of the application of methodological strategies for the teaching-learning process and within the educational field, since it serves as support for teachers so that they can reach their educators with correct knowledge. , that is why this research is titled as: "Incidence of the methodological strategies for teaching-learning of the subject Entrepreneurship and Management in the First Year of Unified General Baccalaureate of the Educational Unit" San Camilo ". The general objective: To determine the incidence of the application of methodological strategies in the teaching-learning of the subject of Entrepreneurship and Management of the students of the first year of the baccalaureate (BGU) of the Educational Unit "San Camilo". The specific hypotheses that have guided the present investigation are: 1) It would greatly affect the non-application of methodological strategies in the teaching-learning process in the subject of Entrepreneurship and Management of the students of the first year of the baccalaureate (BGU) of the Educational Unit "San Camilo". 2) Underlining the importance of properly applying the methodological strategies would improve the academic performance of the students of the first year of baccalaureate (BGU) in the subject of Entrepreneurship and Management of the Educational Unit "San Camilo". 3) By means of the application of a didactic guide the incidence that the methodological strategies in the process of teaching-learning in the subject of Entrepreneurship and Management of the students of the first year of baccalaureate (BGU) of the Educational Unit "San Camilo" will be identified " To carry out this research, the use of methodologies such as field and applied research was used, based on techniques such as direct observation, interview, questionnaire and surveys, which were addressed to teachers and students in the first year of the baccalaureate. , also to the personnel of the administrative area